Aplikasi Iklan Baris Online menggunakan Arsitektur REST Web Service - Yuli Fauziah (Telematika, 2013)
An organization requires an integration if composed of members who live in differentplaces. Organization requires the automation of business processes by exchanging businessdocuments from applications and system platforms are different, both inside or outside the areaof the organization. In this study, an application will be prepared by applying web servicetechnology utilizing REST Web Service Arsitecture, where the server and client can interact witha unified interface, server and client will menghost resource to consume resources provided bythe server. Research is organized so that the business processes that occur when a consumer(client) do a query or search items, integrated with web applications. Server provides a clientAPI which is then utilized. Client in this application is a web application. After receiving datafrom the client, the server and then disseminate the information needs of the goods in questionto all members.Keywords : Web Services, REST, Arsitecture, Client, Server